Postpartum thyroid disorders - Azizi, Fereidoun (Annals of Thyroid; Vol 3 (May 2018): Annals of Thyroid, 2018)
During the postpartum period, there is exacerbation of immune reactivity leading to autoimmune diseases. Two distinct thyroid autoimmune disorders, i.e., postpartum thyroiditis (PPT) and Graves’ disease (GD) may be seen 3–12 months after delivery. PPT is more common and may have various clinical presentations ranging from hypo-or hyperthyroidism per se to transient hyperthyroidism followed by hypothyroidism. Although many patients attain euthyroidism in the second year postpartum, chances of recurrent thyroiditis is very high following later pregnancies. In addition, long term follow-ups of patients with PPT have shown permanent hypothyroidism in about 50% of these patients. GD occurs less frequently than PPT, but must be distinguished from the thyrotoxic phase of the latter. More severe clinical presentations, high values of radioiodine thyroid uptake, T3 to T4 ratio and thyroid blood flow in Doppler ultrasonagraphy and presence of TSH receptor antibody are in favor of diagnosis of GD. Specialized care of the thyrotoxic breastfeeding mother has been emphasized in this review.